Pengaruh Word of Mouth, E-Word of Mouth dan E-Servqual terhadap Purchase Intention Jasa Ojek Online (GOJEK) di Kabupaten Jember - Kanta Dimas Prayogi; Feti Fatimah; Nursaidah Nursaidah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to see how word of mouth, e-word of mouth, and e-servqual affect buying interest in online motorcycle taxi services (GOJEK) in Jember Regency. Participants in this study were consumers of online motorcycle taxi transportation GOJEK, Jember Regency. People in Sumbersari Sub-district who have downloaded the Gojek application and used it at least twice were included in the sample. Respondents are those who are at least 17 years old. Participants in this study were 100 users of GOJEK online motorcycle taxi services in Jember Regency. The information in this study is based on primary sources. Multiple linear regression analysis is an analytical tool used to determine the effect of independent variables on the dependent variable. The results showed that word of mouth, e-word of mouth and e-servqual had an effect on purchase intention of online motorcycle taxi services (GOJEK) in Jember Regency. It can be concluded that a good word of mouth will increase the purchase intention of GOJEK consumers, a high-quality electronic word of mouth will increase the purchase intention of GOJEK consumers, and GOJEK's consumer purchase intention will increase if e-service quality increases. Keywords: E-Servqual, E- Word of Mouth, Purchase Intention and Word of Mouth